Dynamic router and wavelength algorithm based on a VMC-genetic algorithm and dynamic network load balance in optical network - LI Wei 1; HUANG De-xiu 2; LIU De-ming 1; HE Jun1 (Tongxin xuebao)
A novel dynamic router and wavelength assignment （RWA） algorithm for the dynamic wavelength router optical network （WRON） was presented here. By revising the weight of Dijistra algorithm connected with the network traffic under Poisson distribution, a dynamic weight Dijistra algorithm based on the optical network load balance used for the router searching sub-problem was proposed. In it, the router table was refreshed timely based on the network traffic. For wavelength assignment sub-problem, by revising the mutation and crossover rates of genetic algorithm, a novel quick genetic algorithm called VMCR-GA was used to improve the wavelength searching utility. The effectiveness of this RWA is verified through the simulation on the several networks: it can reduce the network block probability 10% and improve the wavelength utility probability 30%~50% comparing with the RWA with normal genetic （NGA） for router and normal Dijistra algorithm（NDA） for wavelength assignment, And the computing time can reduce dramatically.